Kontekstualisasi Tasyabbuh dalam Fatwa MUI Tahun 2024 Tentang Salam Lintas Agama - Rahman, Aulia; Nasrulloh; Dalle, Muhammad (JURNAL KAJIAN ISLAM MODERN, 2024)
Fatwa is the result of Islamic law exploration on an issue. The MUI fatwa on interfaith greetings has opened up a discussion space on the concept of tasyabbuh. This article seeks to interpret the concept of tasyabbuh contained in the hadith and its contextualization in the MUI fatwa. The research method used is interpretive qualitative research with a literature study model with the object of research being the MUI fatwa number 02 of 2024 Ijtima' ulama commission fatwa. The data were obtained through the e-book of the collection of Ijtima' ulama commission fatwa throughout Indonesia VIII in 2024, from digital journals and related research materials, with the data analysis process using a descriptive review using a historical approach. Source triangulation is used as an effort to maintain the validity of the data. From the results of the study, it was found that first, interfaith greetings according to the MUI are something that should not be used except in an emergency and needed. This is in accordance with the argument of the tasyabbuh hadith which has hasan quality. Second, the hadith about tasyabbuh in the argument of the fatwa requires a contextual approach so that it can minimize pros and cons.